Direct3D rendering cookbook : 50 practical recipes to guide you through the advanced rendering techniques in Direct3D to help bring your 3D graphics project to life /: 50 practical recipes to guide you through the advanced rendering techniques in Direct3D to help bring your 3D graphics project to life. (2014) - Unknown
No abstract available